The perception of HIV self-testing and willingness to use mHealth for HIV prevention among Black men who have sex with men in Iowa, United States: A qualitative study - Oluwaseun Abdulganiyu Badru; Oluwafemi Atanda Adeagbo (Digital Health)
Objective The World Health Organization approved HIV self-test (HIVST) to break the barriers to HIV testing. Black men who have sex with men (Black MSM) in the United States are less likely to test for HIV or link to care due to several factors, such as stigma and distance. We explored Black MSM's knowledge of HIVST and their willingness to use a mobile application (mHealth) to link to HIV care and engage with health providers. Methods Between March and September 2023, we interviewed 12 Black MSM in small urban areas and explored HIVST awareness and willingness to use mHealth. Participants were recruited through purposive and snowball sampling. The data were analyzed inductively. Results The age range was 20–42 years. Participants had mixed knowledge of HIVST. The barriers to HIVST uptake are poor knowledge of HIVST, lack of adequate medical insurance to access HIVST kits, and concerns about the efficacy of HIVST kits. Black MSM were willing to link to care via mHealth but expressed concerns related to safety, confidentiality, and the risk of HIV stigma. Participants recommended wider awareness via social media and that the proposed mobile application has a simple interface for ease of use. Conclusion To encourage uptake among Black MSM, the Iowa Department of Health and Human Services should make HIVST accessible (low-cost or free). The proposed mHealth should be developed with a simple and interactive interface, including images and videos to guide HIVST and linkage to health professionals for assistance.